(untitled) (Journal of Parents and Teachers, 2021)
Initiative 8 "Training for work" of the International Federation of Faith and Joy, FIFyA, has been developing a proposal to strengthen technical-technological and comprehensive education, focused on improving employability and job placement for employment, self-employment and entrepreneurship of its students in technical training centers in 23 countries.